Analysis of Microstructural Changes, Morphology and Optical Properties of the Surface of Copper Oxide Thin Layers due to Annealing for Use in Optoelectronic Devices - F. Soleymani (Journal of Advanced Materials in Engineering)
In this study, the effect of thermal annealing on copper oxide thin films was investigated. The surface properties of copper thin films were examined with the goal of employing them as active layers in optoelectronic devices such as solar cells and optical detectors. Thin layers of copper oxide were deposited on glass substrates by spin coating method. The samples were annealed in air at atmospheric pressure and at different temperatures from 200°C to 600°C. The microstructural, morphological, and optical properties of the surface of thin films were studied by diagnostic techniques such as X-ray diffraction, Raman spectroscopy, ultraviolet-visible absorption spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The thickness of copper oxide layers was about 760 nm. The results indicated that the degree of crystallinity improves with increasing annealing temperature, while the values of the strain and dislocation density decrease. XPS analysis showed that deposited copper oxide films have Cu1+ (Cu2O) and Cu2+ (CuO) compounds, and CuO concentration increases with increasing the annealing temperature. Ultraviolet-visible  absorption spectroscopy showed that the thin films are absorbent in the visible region and transparent in the near-infrared region. As the annealing temperature increases above 400 °C, the reflection spectrum changes due to the increase in scattering caused by the growth of crystallite size and surface roughness.